Handbook of Philosophical Logic
XIV, 310 p.
Keywords: This book is indispensable to any advanced student or researcher using logic in these areas. The chapters are comprehensive and written by major figures in the field. Topics include, Belief Revision, Refutation Systems in Propositional Logic, Quantifier Scope in Formal Linguistics and Non-deterministic Semantics for Logical Systems.